Pengaruh Time Budget Pressyre, Pengalaman Auditor dan Due Profesional Care terhadap Kualitas Audit dengan Fee Audit sebagai Variabel Moderasi (Studi Kasus Kantor Akuntan Publik di Kota Medan) - Tengku Nurhaliza Hanim; Mhd. Karya Satya Azhar; Rizki Filhayati Rambe (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to determine whether time budget pressure, auditor experience and due profesional care affect audit quality and whether audit fees can moderate the variables in this study. This type of research uses quantitative associative research with data collection techniques in the form of closed questionnaires obtained from questionnaire data sources, namely auditors in the city of Medan. The results of this study show Time budget pressure does not affect audit quality, Auditor experience does not affect audit quality, Due profesional care affects audit quality, Audit Fees cannot moderate the effect of Time budget pressure. on Audit Quality, Audit Fee cannot moderate the effect of Auditor Experience on Audit Quality, Audit Fee cannot moderate the effect of Due profesional care on Audit Quality